A Trust Based Information Dissemination Model for Evaluating the Effect of Deceptive Data - Yi Hu; Zhichun Xiao; Panda, B. (2007 40th Annual Hawaii International Conference on System Sciences (HICSS'07), 2007)
This research studies the problem of evaluating the effect of deceptive data based on the information flow network and the Web of trust. We present an information dissemination model that illustrates the prerequisite for dissemination of information based on the subject and object trusts. To evaluate the effects of deceptive data accurately, we offer a quantitative model that is utilized to calculate to what extent the subjects in the information flow network are affected. The algorithm for evaluating the spread of deceptive data is provided and the time complexity of the algorithm is also analyzed